Relationship between teachers’ work load and students’ academic performance in senior secondary schools in Irepodun Local Government, Kwara State, Nigeria. - Ogundare, A. Adebimpe; Ambode , A. Benard; Babalola, F. Emmanuel (Kashere Journal of Education, 2023)
The study examined the relationship between workload of teachers and academic performance of students in some selected secondary schools in Irepodun Local Government. The study adopted correlational research design. One hundred and twenty respondents were picked at random from twelve secondary schools (six public schools and six private schools). The data was collected from respondents via questionnaire and Achievement Test in Biology. Statistical Package for Social Scientists (SPSS) was used to evaluate the data collected between private and public secondary schools; Pearson's Product Moment Correlation and t-test Analysis were used to determine the impact of instructors' workload on students' academic achievement. According to the findings, there was a strong negative relationship between teacher workload and student academic performance. It was further discovered that there was a considerable disparity between students’ academic performance in public and private secondary schools. The findings also suggested that science teachers (Including biology) should only teach in accordance with the directive of 1:35 teacher-students ratio by National Policy of Education, as a result, teachers will be able to manage with the workload's stress. It was also recommended that government and other proprietors of Kwara state under the education ministry should employ teachers adequately as likely to conquer the problem in public schools and also to advance the value of teaching-learning development in secondary schools.